Roadmap for the Development and Implementation of Entrustable Professional Activities to Enable Effective Clinical Training - Saurabh RamBihariLal Shrivastava; Shubhada Gade; Sunita Vagha (Contemporary Clinical Dentistry)
In the field of clinical training, entrustable professional activities (EPAs) generally deal with those activities that health-care professionals will be encountering in their routine practice, and thus exposure to these activities prepares them for their future clinical practice. Workplace-based assessment tools have been used to assess the progress of medical students across these defined EPAs. The act of development of EPAs essentially requires the adoption of a systematic process to identify and define the core tasks and responsibilities that medical students must be able to perform independently in a specific specialty. The process of integration of EPAs into the medical school curriculum essentially requires systematic planning and implementation to ensure that students get an adequate number of opportunities to develop and demonstrate the desired competencies. In conclusion, EPAs provide an excellent framework for transforming medical education by preparing medical students to be ready for the complexities of health-care delivery.